Un dispositif d’accès et de partage des avantages sans peuple autochtone ni communauté locale ou les omissions de la loi française pour la reconquête de la biodiversité - Pierre-Alain Collot (VertigO)
Title V of the law for the reconquest of biodiversity promulgated on 08 August 2016 aims to transpose into national law the Nagoya Protocol and the Regulation 511/2014 of the European Parliament and the Council of 16 April 2014. Rather than 'to support the notion of indigenous and local community or even to take into account the autonomous character of the notion of local community, the legislator has made the choice to use the notion of community of inhabitants. The notion of local community, which is specific to environmental law, is nevertheless able of satisfying the requirements of constitutional jurisprudence since it does not consist of a community of origin, culture, language or belief. Beyond the logic inherent in the law of 08 August 2016, the recognition of local communities at the heart of the access and benefit-sharing mechanism must make it possible to correct the multiple shortcomings both in terms of access to genetic resources and traditional knowledge with regard to the sharing of benefits arising from their use.